Ribavirin Quantification in Combination Treatment of Chronic Hepatitis C - Larrat, Sylvie (American Society for Microbiology, 2003)
Ribavirin in combination with alpha 2 interferon is the consensus treatment for chronic hepatitis C. However, recent preliminary pharmacological studies have suggested that the bioavailability of ribavirin displays great interindividual variability. In order to monitor serum ribavirin levels during combination treatment, we developed and validated a quantitative assay using an approach adaptable for routine hospital laboratories. The method involved solid-phase extraction on phenyl boronic acid cartridges followed by high-performance liquid chromatography with a C(18)-bonded silica column and a mobile phase containing 10 mM ammonium phosphate buffer (with the pH adjusted to 2.5) and UV detection (207 nm). The sensitivity, recovery, linearity of the calibration curve, intra- and interassay accuracies, precision, and stability at 4°C were consistent with its use in the laboratory routine. In addition, other nucleoside analogues sometimes used with ribavirin in patients coinfected with hepatitis C virus (HCV) and human immunodeficiency virus did not interfere with the quantification of ribavirin levels. The ribavirin concentration was quantified in 24 serum samples from patients with chronic hepatitis C treated with a combination of ribavirin and alpha 2 interferon. The mean serum ribavirin concentration was 2.67 ± 1.06 μg/ml (n = 24) at week 12 of treatment (W12) and 3.24 ± 1.35 μg/ml (n = 24) at week 24 of treatment (W24). In addition, ribavirin concentrations displayed high interindividual variabilities: the coefficients of variation of the serum ribavirin concentrations adjusted to the administered dose were 44 and 48% at W12 and W24, respectively. Moreover, the ribavirin concentration was higher in patients with a sustained virological response (n = 11) than in patients with treatment failure (n = 13), with significant intergroup differences at W12 (P = 0.030) and W24 (P = 0.049). The present study describes a simple analytical method for the quantification of ribavirin in human serum that could be a useful tool for the monitoring of ribavirin concentrations in HCV-infected patients in order to improve the efficacy and safety of therapy with ribavirin plus interferon.